RECORDS MANAGEMENT PRACTICES IN GHANAIAN TERTIARY INSTITUTIONS: A CASE STUDY OF GHANA COMMUNICATION TECHNOLOGY UNIVERSITY - Ameyaw, S.; Frempong-Kore, A. (UDS International Journal of Development, 2021)
This study was conducted to ascertain records management practices at the Ghana Communications Technology University (formerly Ghana Technology University College) a mid-sized Ghanaian public university located in Accra. All the staff at the Admissions and Records departments participated in the study. This comprised two (2) heads of department and seven (7) senior staff from both departments. The face-to-face interviews were employed as a data collection instrument for this study. The findings indicated that the University has neither a policy to regulate the management of students’ records nor a professional archivist to manage records. However, the head of the Records office was given a three-day training on the assumption of office. It was revealed that the head of admissions, as well as all the staff of the two departments, had never been given any training. There were some challenges impeding records management in the Admissions and Records officesâ€“ among them are; lack of adequate staff, inadequate storage equipment, lack of periodic training, lack of policy to guide records management and inability of students to furnish the Admission office with the needed information. It was recommended that the University should employ a professional archivist to manage student records, provide adequate storage facilities, organise periodic training for staff as well promulgate a policy to guide records management in the Admissions and Records offices. Keywords: Accra Campus, Records, Management, Practices, Ghana Communication Technology University